2010
DOI: 10.1371/journal.pone.0009030
|View full text |Cite
|
Sign up to set email alerts
|

Primary Metabolism of Chickpea Is the Initial Target of Wound Inducing Early Sensed Fusarium oxysporum f. sp. ciceri Race I

Abstract: BackgroundBiotrophic interaction between host and pathogen induces generation of reactive oxygen species that leads to programmed cell death of the host tissue specifically encompassing the site of infection conferring resistance to the host. However, in the present study, biotrophic relationship between Fusarium oxysporum and chickpea provided some novel insights into the classical concepts of defense signaling and disease perception where ROS (reactive oxygen species) generation followed by hypersensitive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 86 publications
2
52
0
Order By: Relevance
“…ACO1 (ACC oxidase1) regulates ethylene biosynthesis and cell death [57]. Upregulation of ACO1 in susceptible plants presumably elicits cell death, which according to our previous studies was reported to lead to susceptibility against Foc1 [15]. ASN (Glutamine dependent asparagines synthase 1) regulates primary nitrogen metabolism that fuels myriad basic metabolic activities during pathogen infection [58].…”
Section: Discussionmentioning
confidence: 99%
“…ACO1 (ACC oxidase1) regulates ethylene biosynthesis and cell death [57]. Upregulation of ACO1 in susceptible plants presumably elicits cell death, which according to our previous studies was reported to lead to susceptibility against Foc1 [15]. ASN (Glutamine dependent asparagines synthase 1) regulates primary nitrogen metabolism that fuels myriad basic metabolic activities during pathogen infection [58].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many studies performed on M. truncatula, soybean, pea, chickpea, peanuts, and common bean provided insight into the molecular basis of their resistance to several legume pathogens including Fusarium oxysporum, Aphanomyces euteiches, Phytophthora sojae, Didymella pinodes, Ascochyta rabiei, Phakopsora pachyrhizi, Peronospora viciae f.sp. pisi, pea seed-borne mosaic virus, bean common mosaic virus, common bacterial blight, Orobanche crenata, Phelipanche aegyptiaca, Heterodera goettingiana, Spodoptera exigua or Helicoverpa armigera (Nyamsuren et al, 2003;Gao et al, 2004;Cho et al, 2005;Cadle-Davidson and Jahn, 2006;Nimbalkar et al, 2006;Die et al, 2007;Choi et al, 2008;Darwish et al, 2008;Singh et al, 2008;Gupta et al, 2009Gupta et al, , 2010Hiraoka et al, 2009;Soria-Guerra et al, 2010;Shi et al, 2011;Veronico et al, 2011;Feng et al, 2012;Huang et al, 2012a,b;Jaiswal et al, 2012;Xu et al, 2012;Rispail et al, 2013;Toyoda et al, 2013).…”
Section: B Transcriptomicsmentioning
confidence: 99%
“…Genome-wide expression profiling of plants infected with Fusarium oxysporum has been reported in several crop plant species, including cotton (Dowd et al 2004), chickpea (Gupta et al 2010) and tomato (Amaral et al 2008). However, no similar study has been reported in watermelon.…”
Section: Introductionmentioning
confidence: 99%